CGIAR Innovation Packages and Scaling Readiness (IPSR) - Schut, Marc (CGIAR System Organization, 2022)
Overview of CGIAR Innovation Packages and Scaling Readiness (IPSR), presented at the CGIAR week of science and practice of scaling agrifood system innovation on 22 November 2022.